Dynamics of longitudinal Hawaiian hotspot motion and the formation of the Hawaiian-Emperor Bend - Jie Zhang; Jiashun Hu (Proceedings of the National Academy of Sciences, 2025)
Formation of the Hawaiian-Emperor Bend has been a key geological puzzle that involves both plate tectonics and plume dynamics. Constrained by paleomagnetic data, southward hotspot motion has been considered a major contributor to the formation of the bend, but the role of longitudinal hotspot motion remains largely overlooked. Here, we analyze the Hawaiian hotspot motion using plate kinematics and geographical distances between hotspot tracks. Both analyses indicate a substantial longitudinal Hawaiian hotspot motion. Further application of global mantle convection models reveals a westward (by ~6°) and then an eastward (by ~2°) hotspot drift in addition to the southward motion before and after the bend, with the westward motion primarily controlled by the intraoceanic subduction in Northeast Pacific. We find that both the westward and southward motion are required to fit the seamount chain, with the former contributing a substantial amount of ~20 degrees to the bend angle, no less than the latter, challenging traditional views. Combined with a geodynamically predicted Pacific Plate motion change at 47 Ma, our model provides a nearly perfect fit to the seamount chain. This result suggests that the Hawaiian plume conduit is tilted toward the southwest, providing a strong indication for the source of the Hawaiian plume that has long been debated among seismological studies.